Geostrategy For Moving The Archipelago’s Capital City: Analysis Through Strategic Intelligence Components - Rahman, Denizar; Hanita, Margaretha; Salya, Sundawan (Journal Research of Social Science, Economics, and Management, 2024)
The relocation of Indonesia’s capital (IKN) from Jakarta to Nusantara is an ambitious undertaking with far-reaching strategic implications for the nation. This study examines the capital relocation through the framework of nine strategic intelligence components: ideology, politics, economy, socio-culture, defense and security, law, information, technology, and the environment. The analysis integrates findings from previous research (synthetic analysis) with data gathered from news sources and field observations (narrative analysis). This study employs a qualitative approach using synthetic analysis and narrative analysis methods. The synthetic analysis was conducted by reviewing and summarizing previous research related to the IKN relocation, while the narrative analysis involved gathering data from various sources, such as news reports, official documents, and field observations. The conclusion of this research indicates that the relocation of the IKN to Nusantara is a strategic, complex, and multidimensional initiative, holding significant potential benefits but also facing various challenges.